1983
DOI: 10.1172/jci111091
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G inhibitor of thyroid-stimulating antibody is a cause of delay in the onset of neonatal Graves' disease.

Abstract: A B S T R A C T Studies were carried out with the serum IgG from a mother and her two children who developed neonatal Graves' disease several weeks after birth. The maternal IgG: (a) stimulated the human thyroid in vitro, but maximal stimulation was found only with dilution of the IgG; (b) was very potent in the long-acting thyroid stimulator (LATS)-protector assay, but only when an inhibitor of the system was diluted out; (c) inhibited a standard preparation of LATS in the mouse bioassay; (d) was biphasic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 15 publications
2
45
1
1
Order By: Relevance
“…Present evidence suggests that the sera of some patients with autoimmune thyroid disease contain a mixture of stimulatory or inhibitory TSH receptor antibodies (1,7,20). Although the epitopes for these antibodies are unknown, the present concept is that they correspond to the TSH binding site on the TSH receptor.…”
Section: Discussionmentioning
confidence: 84%
“…Present evidence suggests that the sera of some patients with autoimmune thyroid disease contain a mixture of stimulatory or inhibitory TSH receptor antibodies (1,7,20). Although the epitopes for these antibodies are unknown, the present concept is that they correspond to the TSH binding site on the TSH receptor.…”
Section: Discussionmentioning
confidence: 84%
“…Serum dilution also has a major effect on the detection of TSAb. In the presence of high TBAb activity, Zakarija and McKenzie observed that TSAb activity may emerge only after serum dilution or after the decline in neonatal TSHR Ab levels following transplacental passage from the mother (35).…”
Section: Figurementioning
confidence: 99%
“…This time period is 36-72 hours for methimazole (25). The clinical signs and symptoms may be delayed up to 7-10 days because of antithyroid drugs or TSHR blocking antibodies found in the serum (26). In another study, it was observed that the clinical picture appeared in the postnatal 1 st -3 rd days in babies of mothers who were not using medication, and in the postnatal 7 th -17 th days in the other babies (27).…”
Section: Clinical Picturementioning
confidence: 99%
“…Subsequently, the level in the fetus gradually increases and exceeds the mother's level in the term newborn (14). Although it has been proposed that the clinical picture may start from the 21 st week when the antibody level increases and the fetal TSH receptors become responsive, the picture of fetal hyperthyroidism generally becomes prominent in the [26][27][28] th weeks (5). Both sexes are affected equally.…”
Section: Treatment Approachesmentioning
confidence: 99%